Effect of surface modification of silicon carbide nanoparticles on the properties of nanocomposites based on epoxidized natural rubber/natural rubber blends. Issue 37 (7th June 2017) - Utara, Songkot; Jantachum, Punyarat; Sukkaneewat, Benjatham
ABSTRACT: Improvement of the properties of rubber nanocomposites is a challenge for the rubber industry because of the need for higher performance materials. Addition of a nanometer‐sized filler such as silicon carbide (SiC) to enhance the mechanical properties of rubber nanocomposites has rarely been attempted. The main problem associated with using SiC nanoparticles as a reinforcing natural rubber (NR) filler compound is poor dispersion of SiC in the NR matrix because of their incompatibility. To solve this problem, rubber nanocomposites were prepared with SiC that had undergone surface modification with azobisisobutyronitrile (AIBN) and used as a filler in blends of epoxidized natural rubber (ENR) and natural rubber. The effect of surface modification and ENR content on the curing characteristics, dynamic mechanical properties, morphology and heat buildup of the blends were investigated. The results showed that modification of SiC with AIBN resulted in successful bonding to the surface of SiC. It was found that modified SiC nanoparticles were well dispersed in the ENR/NR matrix, leading to good filler‐rubber interaction and improved compatibility between the rubber and filler in comparison with unmodified SiC. The mechanical properties and heat buildup when modified SiC was used as filled in ENR/NR blends were improved. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45289. Abstract :